The incremental information content of half-yearly earnings data releases by South African companies - R. F. Knight; J. F. Affleck-Graves (South African Journal of Business Management, 1986)
In this article the information content of half-yearly earnings announcements is examined. Both annual and interim announcements are examined using the Abnormal Performance Index (API) methodology and it is shown that both sets of announcements provide incremental information. The results obtained indicate that, on average, the second-half announcements prove more informative than the second-half reports. Nevertheless, the first-half reports are still shown to provide significant incremental information. In addition, the results obtained are consistent with previous results in the sense that the API plots indicate asymmetrical behaviour with respect to 'good news' and 'bad news' announcements. Finally, it is shown that an investment strategy based on a foreknowledge of half-yearly earnings forecast errors provides higher returns than a similar strategy based on annual earnings forecast errors. This clear indication of the information content of half-yearly announcements leads the authors to speculate on whether quarterly reporting might not be in the interests of shareholders on the Johannesburg Stock Exchange.
Keywords: 650